Hypoxia Inducible Factor-1–Independent Pathways in Tumor Angiogenesis - Mizukami, Yusuke; Kohgo, Yutaka; Chung, Daniel C. (Clinical cancer research, 2007)
Among the factors that can stimulate angiogenesis, vascular endothelial growth factor has emerged as one of the most important, and inhibition of vascular endothelial growth factor has recently shown efficacy in the treatment of advanced colorectal cancer. Hypoxia develops within solid tumors and is one of the most potent stimuli of vascular endothelial growth factor expression. This effect is mediated primarily by hypoxia inducible factor-1 (HIF-1), often considered a master regulator of angiogenesis in hypoxia. Consequently, inhibition of HIF-1 has been proposed as a strategy to block tumor angiogenesis therapeutically. However, accumulating evidence indicates that HIF-independent pathways can also control angiogenesis. This review highlights some of the key signaling pathways independent of HIF-1 that can stimulate angiogenesis in hypoxia. Understanding the full spectrum of molecular pathways that control tumor angiogenesis is critical for the optimal design of targeted therapies.